Metacognitive and Direct – Instructional Strategies as Determinants of Reading Skills among Students with Learning Disabilities in Secondary Schools in Ogun State, Nigeria (2011)
Reading skills are vital to successful learning in all school subjects. Students with learning disabilities are known to have difficulties in reading. Studies have been carried out on the usage of conventional methods in improving the comprehension skills of students with learning disabilities, but not much has been done on the use of metacognitive and direct-instructional strategies. This study, therefore, investigated the differential effectiveness of metacognitive and direct-instructional strategies on the comprehension skills of students with learning disabilities. The moderating effects of gender and age on the dependent variables were also explored. The study adopted a pretest-posttest, control group quasi experimental design with 3 x 2 x 2 matrix. The participants comprised 75 Junior Secondary II students with learning disabilities identified through the use of Myklebust‟s Pupils Rating Scale. They were assigned to two experimental groups (metacognitive strategies and direct-instructional method) and the control group. Three research instruments were used: The Pupils Rating Scale (r = 0.97), Reading Comprehension Ability Screening Test (r = 0.77) and Reading Comprehension Skill Test for students with Learning Disabilities (r = 0.79). Seven hypotheses were tested at 0.05 level of significance. Data collected were analysed using mean and standard deviation, Analysis of Covariance and Scheffe post hoc test. Graphs were used to disentangle the second order interaction effect of treatment, gender, and age. There was a significant main effect of treatment on the comprehension skills of participants. Students in metacognitive strategies group had highest mean score (x= 32.97), followed by direct-instruction (x= 31.55) while those in the control group (conventional methods) had the least performance ( x = 25.61). The observed mean difference among the three groups was statistically significant, F (2, 62) = 4.62; p < 0.05). The effect size of treatment was 13.0% and classified as moderate. There was no significant main effect of age and gender on the students‟ comprehension skills and no significant interaction effect, that is, treatment and gender, treatment and age, age and gender. However there was a significant interaction effect of treatment, age and gender (F2,62) = 3.79; p < 0.05. The effect size was 10.9 % which was also classified as moderate. Late adolescents in all the treatment groups had higher comprehension skills than their early adolescent colleagues. Metacognitive and direct-instructional strategies were effective in enhancing reading comprehension skills of students with learning disabilities. Metacognitive instruction was however found to be more effective in teaching reading comprehension skills to students with learning disabilities. Therefore, to foster greater comprehension skills among students with learning disabilities, metacognitive and direct-instructional methods should be applied. More specialist teachers in learning disabilities should be trained to assist students with reading comprehension problems.